Increased Incidence and Plasma-Biofilm Formation Ability of SCCmec Type IV Methicillin-Resistant Staphylococcus aureus (MRSA) Isolated From Patients With Bacteremia - Hamada, Masakaze; Yamaguchi, Tetsuo; Sato, Ayami; Ono, Daisuke; Aoki, Kotaro; Kajiwara, Chiaki; Kimura, Soichiro; Maeda, Tadashi; Sasaki, Masakazu; Murakami, Hinako; Ishii, Yoshikazu; Tateda, Kazuhiro (Frontiers in Cellular and Infection Microbiology, 2021)
In Japan, Staphylococcal cassette chromosome mec (SCCmec) type IV methicillin-resistant Staphylococcus aureus (MRSA) is an increasingly prominent cause of bacteremia, but the virulence of most of these strains is unclear. We aimed to investigate the relationship between the molecular characteristics and the ability to form biofilms in the presence of blood plasma (plasma-biofilms) of MRSA strains isolated from bloodstream infections. In this study, the molecular characteristics and biofilms of MRSA strains isolated from blood cultures between 2015 and 2017 were analyzed by PCR-based assays, crystal violet staining, and confocal reflection microscopy methods. Among the 90 MRSA isolates, the detection rate of SCCmec type II clones decreased from 60.7 to 20.6%. The SCCmec type IV clone replaced the SCCmec type II clone as the dominant clone, with a detection rate increasing from 32.1 to 73.5%. The plasma-biofilm formation ability of the SCCmec type IV clone was higher than the SCCmec type II clone and even higher in strains harboring the cna or arcA genes. Plasma-biofilms, mainly composed of proteins, were formed quickly and strongly. Our study demonstrated the increased plasma-biofilm formation ability of SCCmec type IV strains.